A study on the Quality of Life (QoL) and depression among antenatal women / Nik Nurafifah Nik Zaidi, Nurfasihah Zulkifli and Nuruljannah Mohamad Rodzi - Nik Zaidi, Nik Nurafifah; Zulkifli, Nurfasihah; Mohamad Rodzi, Nuruljannah (2019)
The research study that have been conducted on antenna! women. The objectives of the study are to identify the quality of life during antenatal stage, to identify depression stage among antenatal women and to compare quality of life between non-depressed pregnant women and depressed pregnant women. From the study, method of Descriptive Analysis and Hotelling T Square was implemented. For descriptive statistics most of the antenatal women originate from urban area. The most number of pregnancy women are in the early stage of pregnancy which is first trimester followed by second trimester and third trimester. Meanwhile, most of the respondents gave birth normally and not many of them ever experienced miscarriage. For the colour system used by the hospital to grade all antenatal women based on the level of severity of risk factors, green is the highest which means the mothers only required monitoring by a senior nurse. In analysing the result of Hotelling T square, the value of test statistics obtained is 567.866 which is larger than the critical value with the value of 15.507 respectively. Conclusion can be made from the result is that, there is a difference in the eight life domains between depression and no depression among antenatal women. It is proven that for pregnant women who is suffering from depression will have poor quality of life and vice versa. For the recommendations, an initiative have been found to handle the independent variable in this research study precisely. For future studies, Government and hospital management should introduce screening for depression as part of routine antenatal assessments in both public and private health facilities. Not only that, hospital management should check on the antenatal women both on their physical and mental health since early detection of depression is crucial in order to avoid its further consequences.